GAMBARAN HISTOLOGIK HATI TIKUS WISTAR YANG DIBERI VIRGIN COCONUT OIL DENGAN INDUKSI PARASETAMOL - Manatar, Amelia F.; Wangko, Sunny; Kaseke, Marie M. (JURNAL BIOMEDIK : JBM, 2013)
Abstract: Virgin Coconut Oil (VCO) is defined as a multifunction supplement of health. Previous research has proved that it can be used for anti-inflammation, anti-pyretic, anti-oxidant, and for metabolism repairments. This VCO will be biotransformed in the liver. Paracetamol is an analgetic and antipyretic medicine which is usually used for self-medication. Over dosage of paracetamol is potentially destructive for the liver, which is the major detoxification organ. This study aimed to find out the histological changes of wistar livers treated with VCO after being induced with paracetamol. This was an experimental study using the post-test-only control group design. This study was conducted for 12 days. As subjects, we used 22 male wistars divided into five groups: negative control group (KN); positive control group (KP) treated with toxic dosages of paracetamol (2.5 g/kg BW/day) from day 8 to 12; and three treatment groups (P1, P2, and P3) given VCO 1 ml, 5 ml, and 10 ml per kg BW/day consecutively for 12 days, added with the paracetamol 2.5 g/kg BW/day from day 8 to 12. Some wistars from each group were terminated on day 10 and the others on day 13. Their livers were examined for macroscopic and microscopic observations. The histological changes found were: lipid degeneration, hydrophic degeneration, and necrosis of hepatocytes in the KP, P1, P2, and P3. The P2 showed less liver destruction than KP, P1, and P3. Moreover, hepatocyte regeneration was found in P1 and P2. Conclusion: Paracetamol induction of toxic dosages 2.5 g/kg BW resulted in histological changes of the wistar livers (hydrophic degeneration, fatty degeneration, and hepatocyte necrosis). Treatment with VCO 1 ml and 5 ml/kg BW/day could diminish the changes and stimulate the regeneration of hepatocytes. However, with a maximal dosage of 10 ml/kg BW/day, VCO worsened the injured liver marked by diffuse fatty degeneration of the livers. Keywords: liver destruction, paracetamol, virgin coconut oil.    Abstrak: Virgin Coconut Oil (VCO) diyakini memiliki banyak fungsi yang berkaitan dengan kesehatan. VCO berkhasiat sebagai anti inflamasi, anti piretik, antioksidan, dan memperbaiki fungsi metabolisme tubuh. Parasetamol merupakan obat analgetik dan antipiretik yang banyak digunakan. Toksisitas akut dari obat ini berpotensi menimbulkan kerusakan hati. Penelitian ini bertujuan untuk melihat gambaran histologik hati tikus wistar yang diberi VCO disertai induksi parasetamol. Penelitian ini bersifat eksperimental dengan rancangan penelitian the post test only control group design. Subyek penelitian yaitu dua puluh dua ekor wistar jantan dibagi dalam lima kelompok, yaitu: kontrol negatif (KN), kontrol positif (KP) yang diberi parasetamol dosis toksik 2,5 g/kg BB/hari pada hari ke 8-12, dan kelompok perlakuan 1, 2, dan 3 (P1, P2, dan P3) yang diberi VCO masing-masing kelompok perlakuan 1 ml, 5 ml. dan 10 ml per kg BB/hari selama 12 hari dengan pemberian parasetamol 2,5 g/kg BB/hari dimulai pada hari ke 8-12. Hasil penelitian menunjukkan perubahan gambaran struktur histologik hati berupa degenerasi lemak, degenerasi hidropik, dan nekrosis pada kelompok KP, P1, P2, dan P3. Kelompok P2 memperlihatkan lebih sedikit perubahan histologik hati dibandingkan kelompok KP, P1 dan P3. Aktivitas regenerasi hepatosit ditemukan pada kelompok P1 dan P2. Simpulan: Induksi parasetamol dosis toksik 2,5 g/kg BB mengakibatkan perubahan histologik hati berupa degenerasi hidropik, degenerasi lemak, dan nekrosis hepatosit. Pemberian VCO dosis 1 ml/kg BB dan 5 ml/kg BB dapat mengurangi terjadinya perubahan tersebut serta mampu merangsang regenerasi hepatosit secara cepat sedangkan pemberian VCO dosis maksimal 10 ml/kg BB memperparah cedera hati dengan terjadinya degenerasi lemak yang difus. Kata kunci: kerusakan hati, parasetamol, virgin coconut oil.